Exploring Children's Requirements for Game-Based Learning Environments. (3rd August 2008) - Nousiainen, Tuula; Kankaanranta, Marja
Abstract : End users' expertise in the development of new applications is acknowledged in user-centered and participatory design. Similarly, children's experience of what they find enjoyable and how they learn is a valuable source of inspiration for the design of products intended for them. In this paper, we explore experiences obtained from collaboration with elementary school children in the design of learning environments, based on three projects and three requirements gathering techniques. We also discuss how the children experienced the participation. The children's contribution yielded useful, both expected and unanticipated, outcomes in regard to the user interface and contents of the learning environments under development. Moreover, we present issues related to design collaboration with children, especially in terms of the children's feeling of ownership over the final outcome.